New species of Polylepis (Rosaceae) from Vilcabamba mountain range (Cusco, Peru) - Mendoza, Wilfredo (2005)
During the study of the genus Polylepis in Peru, one species restricted to the Vilcabamba mountain range, southern Peru was recognized as new and described herein.